Path planning for an autonomous underwater vehicle in a cluttered underwater environment based on the heat method - Sun, Kaiyue; Liu, Xiangyang (Zielona Góra: Uniwersytet Zielonogórski)
This paper proposes a novel autonomous underwater vehicle path planning algorithm in a cluttered underwater environment based on the heat method. The algorithm calculates the isotropic and anisotropic geodesic distances by adding the direction and magnitude of the currents to the heat method, which is named the anisotropy-based heat method. Taking account of the relevant influence of the environment on the cost functions, such as currents, obstacles and turn of the vehicle, an efficient collision-free and energy-optimized path solution can be obtained.
Keywords: autonomous underwater vehicle; path planning; heat method; heat diffusion; cost function